Konstruksi Ideologi Dalam Wacana Video “Darurat Militer”; Analisis Wacana Kritis Pendekatan Norman Fairclough - Ester Reviani Manullang; Hera Chairunisa; Syairal Fahmy Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the discourse surrounding the declaration of a military emergency in Indonesia, focusing on digital media content, particularly videos produced by content creator Ferry Irwandi. This research employs Norman Fairclough's Critical Discourse Analysis (CDA) framework to uncover the ideological constructions and power relations embedded in the discourse. Three videos analyzed include